Non-analgesic effects of opioids: Topical application of Eucerin-based ointment containing opium on the healing process of thermal skin damage in rats. - Omid Mehrpour; Khadijeh Farrokhfall; Kobra Naseri; Samaneh Nakhaee (PLoS ONE)
The present study aimed to investigate the efficacy of different doses of Eucerin-based ointment containing opium compared to routine treatment on experimentally induced burn injury. Male Wistar rats were divided into five experimental groups for topical application: silver sulfadiazine 1% (SSD), Eucerin-based ointment containing opium at concentrations of 0.05%, 0.5%, and 5%, and a Eucerin-based ointment containing 0.05% opium plus SSD (mixed group), following burn wound induction using the comb burn model. An equal volume of different ointments was administered topically. The wound appearances of different groups were photographed at different time points for 21 days. In addition, blood and skin samples were taken 2 and 10 days after thermal injury to assess inflammatory parameters and oxidative stress markers. Also, the liver enzyme activity and kidney function tests were assessed on day 10. The body weight in Opium 5% significantly decreased compared to all other groups after ten days. The wound area was significantly reduced (P<0.05) in three groups: Opium 0.05%, Opium 0.5%, and mixed, compared to the SSD group on days 14 and 21. On day 21, the wound size in the Opium 5% group was significantly larger than that in the SSD group. Significantly lower serum levels of MDA were observed in all groups compared to the SSD group on days 2 and 10. There were no significant differences between treatment groups for concentrations of TNF-α in serum and burned skin samples (p>0.05). The serum concentrations of interleukin-10 in the mixed group were significantly higher compared to the SSD group on day 10. After ten days, groups were not different regarding AST, ALT, and creatinine concentrations (p>0.05). Histopathological analysis revealed that the wound healing efficacy of opium at its lowest concentration (0.05%) surpassed that of silver sulfadiazine (SSD). Furthermore, the combination of 0.05% opium with SSD enhanced the wound repair potential of SSD in burn injuries. This study showed that opium ointment delayed wound closure dose-dependently. Low doses of topical opium ointment and its mixed application with silver sulfadiazine had a protective role in thermal-induced injury.